Synergistic effects of dried Padina sp. and prebiotic on growth, histology, and growth-related gene expression in European seabass (Dicentrarchus labrax) - Metin Yazici (Czech Journal of Animal Science)
This study evaluated the effects of feeding European seabass (Dicentrarchus labrax) that developed from the fingerling to juvenile stage a diet supplemented with a blend of Padina sp. and GroBiotic®-A over a 12-week period. A total of 480 fish (initial weight: 2.08 ± 0.06 g) were randomly allocated to four groups, each comprising three replicates. The fish were fed to satiation with diets containing varying proportions of Padina sp. and GroBiotic®-A: 0% Padina sp. and 0% GroBiotic®-A (0P0G), 1% Padina sp. and 1% GroBiotic®-A (1P1G), 2% Padina sp. and 1% GroBiotic®-A (2P1G), and 4% Padina sp. and 1% GroBiotic®-A (4P1G). The 4P1G group demonstrated significant improvements in growth performance parameters, including final weight, weight gain, and specific growth rate (P < 0.05). However, no significant differences were found in other parameters including feed conversion ratio, visceral somatic index, and survival rate (P > 0.05). Histological analysis of liver and intestinal tissues showed no pathological alterations (P > 0.05); more likely, only adaptive and non-pathological morphological changes such as moderate lipid vacuolisation and preserved mucosal structure were noted. Furthermore, dietary supplementation of the Padina sp. and GroBiotic®-A blend significantly upregulated the expression of growth-related genes, specifically growth hormone and insulin-like growth factor 1 (P < 0.05). These results suggest that the combination of Padina sp. and GroBiotic®-A has a synergistic potential to enhance the growth performance without inducing digestive disturbances. Nevertheless, further studies are recommended to assess its effects on fish grown to market size before commercial application.